2005
DOI: 10.1111/j.1365-2966.2005.09401.x
|View full text |Cite
|
Sign up to set email alerts
|

An old quasar in a young dark energy-dominated universe?

Abstract: Dark energy is the invisible fuel that seems to drive the current acceleration of the Universe. Its presence, which is inferred from an impressive convergence of high-quality observational results along with some apparently sucessful theoretical predictions, is also supported by the current estimates of the age of the Universe from dating of local and high-$z$ objects. In this paper we test the viability of several dark energy scenarios in the light of the age estimates of the high redshift ($z=3.91$) quasar A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
84
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 45 publications
1
84
1
2
Order By: Relevance
“…By comparing photometric data acquired from the Beijing-Arizona-TaiwanConnecticut system with up-to-date theoretical synthesis models, Ma et al [467] obtained the ages of 139 globular clusters (GCs) in the M31 galaxy, in which 9 extremely old GCs are older than the present cosmic age predicted by the 7-year WMAP observations [468]. In addition, the existence of high-z quasar APM 08279+5255 at z = 3.91 [469] is also a mystery [470,471,472]. Using the maximum likelihood values of the 7-year WMAP observations Ω m = 0.272 and h = 0.704, the ΛCDM model can only give a cosmic age t = 1.63 Gyr at redshift z = 3.91, while the lower limit of this quasar's age is 1.8 Gyr.…”
Section: Cosmic Age Testsmentioning
confidence: 99%
“…By comparing photometric data acquired from the Beijing-Arizona-TaiwanConnecticut system with up-to-date theoretical synthesis models, Ma et al [467] obtained the ages of 139 globular clusters (GCs) in the M31 galaxy, in which 9 extremely old GCs are older than the present cosmic age predicted by the 7-year WMAP observations [468]. In addition, the existence of high-z quasar APM 08279+5255 at z = 3.91 [469] is also a mystery [470,471,472]. Using the maximum likelihood values of the 7-year WMAP observations Ω m = 0.272 and h = 0.704, the ΛCDM model can only give a cosmic age t = 1.63 Gyr at redshift z = 3.91, while the lower limit of this quasar's age is 1.8 Gyr.…”
Section: Cosmic Age Testsmentioning
confidence: 99%
“…In Ref. [9] it was investigated whether this model satisfies the current Universe age constraints and allows a considerably older universe at high redshift to be compatible with the existence of some old objects such as the old quasar APM0879+5255 at redshift z = 3.91 [41]. Its age, at that redshift, was estimated as t g = 2.1Gyr.…”
mentioning
confidence: 99%
“…The different evolution of the DM due to its interaction with the DE gives rise to a different expansion history of the Universe and a different evolution of the matter density perturbations which alters the standard structure formation scenario as the latter assumes ρ m ∝ a −3 . In [7,9] the matter density perturbations in interacting models were investigated and in [9] the impact of the interaction on the DM perturbations was used to explain why it is possible, as recently observed [41], for the old quasar APM0879+5255 to exist already at the early stages of the Universe (at z = 3.91). As a comparison, in Figs.…”
mentioning
confidence: 99%
“…Chen and Jing [23] showed that those equations yield accelerating universe solutions without resorting to dark energy. They show that the model not only fits the supernovae data, but also solves the cosmic age problem of old high redshift objects [24]. Whether the cosmological solutions described in the current work would fit empirical results just as well needs to be investigated.…”
Section: Summary and Discussionmentioning
confidence: 99%